P2Y12-inhibitor monotherapy after coronary stenting: are all P2Y12-inhibitors equal?. (3rd August 2022) - van der Sangen, Niels MR; Küçük, I Tarik; ten Berg, Jurriën M; Beijk, Marcel AM; Delewi, Ronak; den Hartog, Alexander W; Appelman, Yolande; Verouden, Niels JW; Kikkert, Wouter J; Henriques, José PS; Claessen, Bimmer EPM
ABSTRACT: Introduction: P2Y12 -inhibitor monotherapy following 1–3 months of dual antiplatelet therapy (DAPT) reduces (major) bleeding without an apparent increase in ischemic events and has therefore emerged as an alternative to 6–12 months of DAPT following percutaneous coronary intervention (PCI). However, there are important differences between the available P2Y12 -inhibitors (clopidogrel, prasugrel, and ticagrelor) as agents of choice for P2Y12 -inhibitor monotherapy. Areas covered: This review critically appraises the evidence for P2Y12 -inhibitor monotherapy after PCI using either clopidogrel, prasugrel, or ticagrelor. Furthermore, we discuss ongoing trials and future directions for research. Expert opinion: P2Y12 -inhibitor monotherapy following 1–3 months of DAPT is an alternative to 6–12 months of DAPT following PCI. Ticagrelor may be considered the current preferred option due to its reliable effect on platelet reactivity and its predominant use in clinical trials. Prasugrel could serve as a useful substitute for those not tolerating ticagrelor, but more research into prasugrel monotherapy is warranted. Alternatively, clopidogrel can be used, although there are concerns of high platelet reactivity, especially when genotyping and/or platelet function testing are not used. Future research will need to address the minimal duration of DAPT before switching to P2Y12 -inhibitor monotherapy and what the optimal antithrombotic therapy beyond 12 months is.